Correlation between directions of movement of internal conversion electron and beta-particle - M. F. Mitrokhovich (Ядерна фізика та енергетика)
Study of the correlation between the motion of conversion electron (as an accompanying particle) and β particle (as the main particle) was performed for the decay of 152Eu on installation to measure double and triple coincidences of γ-quanta with β-particles, electrons and with low energy electrons, including electrons of the secondary electron emission (e0-electrons). The correlation ϒ = (4π/P)dp/dΩ of conversion electron and β-particle was measured by the correlation of Auger electron with β--particle, since the correlation between Auger electron and conversion electron is known and it is large. Based on the measurements of γ, γβ, γ(е0 + β) and γβе0-spectra, it was established that the Auger electron (indirectly also conversion electron) is strongly correlated with the β-particle in the Ω = 0 direction to the forward hemisphere and the correlation ϒ is 6.8(19) for the measurements in the decay of 152Eu. Conditional qualitative scheme for strong correlation between motion of the accompanying particle with the main one, which is due to the current components from the motion of charged particle in states after completion of the main processes, is discussed.